2007
DOI: 10.1002/adfm.200700122
|View full text |Cite
|
Sign up to set email alerts
|

Addressable Protein Patterning via Switchable Superhydrophobic Microarrays

Abstract: We report on a simple process to create a switchable superhydrophobic surface where the water contact angle can be switched from a superhydrophobic state (ca. 167°) to a completely wetted state (< 10°). In the superhydrophobic state, the switchable superhydrophobic surface was resistant to the adsorption of proteins. However, once converted to a wetted state, the same surface promoted protein adsorption. We have developed a novel multicomponent protein‐patterning technique based on this unique property of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 23 publications
0
47
0
Order By: Relevance
“…We performed a BCA assay in order to investigate the effect of surface topography on protein adsorption between topographic cues comparable to what was described elsewhere [39][40][41]. So far just a few studies reported protein adsorption on surfaces exhibiting extreme contact angles [20,42,43]. A comparison of quantitative outcome of these BSA adsorption studies onto smooth and rough surfaces after 24 h is shown in Fig.…”
Section: Protein Adsorption On Surfacesmentioning
confidence: 99%
“…We performed a BCA assay in order to investigate the effect of surface topography on protein adsorption between topographic cues comparable to what was described elsewhere [39][40][41]. So far just a few studies reported protein adsorption on surfaces exhibiting extreme contact angles [20,42,43]. A comparison of quantitative outcome of these BSA adsorption studies onto smooth and rough surfaces after 24 h is shown in Fig.…”
Section: Protein Adsorption On Surfacesmentioning
confidence: 99%
“…Single cells at higher magnification (g, h, i) were grown on the three kinds of substrates for 24 h [68] ; (j)~(o) SEM micrographs showing the morphology of L929 (a and d), ATDC5 (b and e) and SaOs-2 (c and f) and on hydrophobic and superhydrophobic respectively, after 6 days culture [69] 化 学 学 报 综述 图 7 (a) SEM 图像显示大量的血小板粘附在光滑的 PCU 表面 [77] ; (b) 图(a)中放大后的单个血小板 [77] ; (c) SEM 图显示纳米结构超疏水 PCU 表面几乎观察不到血小板 [77] ; (d)图(c)中放大后的单个血小板 [77] ; (e)水 系统中, 油滴在纳米结构 PNIPAAm 表面的接触角 [79] ; (f) 20 和 37 ℃ 下, 纳米结构的 PNIPAAm 表面均显示出低粘附力且几乎没有残留 物 [79] Figure 7 (a) SEM image of the remarkable platelet adhesion on the smooth FPCU film [77] ; (b) Magnified image of a single platelet in (a) [77] ; (c) SEM image of few platelet adhesion the nano-structured superhydrophobic FPCU [77] ; (d) Magnified image of the platelet in (c) [77] ; (e) CAs of droplets on the SINWA-PNIPAAm surface in water, where the surface remained a superoleophobic state [79] ; (f) At 20 ℃ and 37 ℃ , the SINWA-PNIPAAm surface shows a low force and almost no residuum [79] 这与 PS 表面的微纳米结构密切相关. Chen 等 [87] ; (b) MTly-mCherry 细胞在图案表面生长 48 h 后的荧光显微镜图 [90] ; (c) 细胞在微图案表 面培养 24 h 后粘附行为的相衬显微图 [88] ; (d) CHO 细胞固定在超亲水硅纳米线图案内的扫描电镜图 [89] ; (e)~(j) 3T3 细胞在不同粗糙度的含氟聚合 物上培养, 图案区域的表面粗糙度依次为(e) 10 nm, (f) 25 nm, (g) 35 nm, (h) 42 nm, (i) 52 nm, (j) 65 nm. 图中比例尺为 200 μm [91] Figure 8 (a) Combined fluorescence images of a chip patterned with five different anti-IgGs: FITC-conjugated anti-chicken and anti-goat IgG, and TRITC-conjugated anti-mouse, anti-rabbit, and anti-goat IgG [87] ; (b) Fluorescent microscope images of MTly-mCherry cells after growing for 48 h on the array [90] ; (c) Phase-contrast microscopic images of cell adhesion behaviors on the micropatterned surface after cultured for 24 h [88] ; (d) SEM images of CHO cells trapped within the superhydrophilic SiNW patterns [89] ; (e)~(j) 3T3 cells cultured on various roughened fluoropolymers.…”
Section: Figurementioning
confidence: 99%
“…Chen 等 [87] ; (b) MTly-mCherry 细胞在图案表面生长 48 h 后的荧光显微镜图 [90] ; (c) 细胞在微图案表 面培养 24 h 后粘附行为的相衬显微图 [88] ; (d) CHO 细胞固定在超亲水硅纳米线图案内的扫描电镜图 [89] ; (e)~(j) 3T3 细胞在不同粗糙度的含氟聚合 物上培养, 图案区域的表面粗糙度依次为(e) 10 nm, (f) 25 nm, (g) 35 nm, (h) 42 nm, (i) 52 nm, (j) 65 nm. 图中比例尺为 200 μm [91] Figure 8 (a) Combined fluorescence images of a chip patterned with five different anti-IgGs: FITC-conjugated anti-chicken and anti-goat IgG, and TRITC-conjugated anti-mouse, anti-rabbit, and anti-goat IgG [87] ; (b) Fluorescent microscope images of MTly-mCherry cells after growing for 48 h on the array [90] ; (c) Phase-contrast microscopic images of cell adhesion behaviors on the micropatterned surface after cultured for 24 h [88] ; (d) SEM images of CHO cells trapped within the superhydrophilic SiNW patterns [89] ; (e)~(j) 3T3 cells cultured on various roughened fluoropolymers. The surface roughness on the patterned area was (e) 10 nm, (f) 25 nm, (g) 35 nm, (h) 42 nm, (i) 52 nm, (j) 65 nm.…”
Section: Figurementioning
confidence: 99%
“…In particular, this technology was transposed to assess the biological response of 3D biomaterials, by encapsulating cells in arrays of miniaturized hydrogels dispensed onto patterned superhydrophobic substrates [103]. A high-throughput protein microarray was also proposed by Shiu et al [104]. Superhydrophobic Teflon AF substrates were prepared by plasma treatment, and a switchable wetting character that could change from superhydrophobic to superhydrophilic was achieved using the electrowetting technology.…”
Section: High-throughput Chips Based On Surfaces With Extreme Wettabimentioning
confidence: 99%
“…Superhydrophobic Teflon AF substrates were prepared by plasma treatment, and a switchable wetting character that could change from superhydrophobic to superhydrophilic was achieved using the electrowetting technology. Micropatterns were fabricated on these switchable superhydrophobic substrates [104]. Each spot on this microarray can be addressed individually, and different types of proteins or other biomolecules can be deposited on the microarray without losing their activity.…”
Section: High-throughput Chips Based On Surfaces With Extreme Wettabimentioning
confidence: 99%